On the taxonomic status of the harvest mouse Micromys minutus (Rodentia: Muridae) from Vietnam - Abramov, Alexei V.; Meschersky, Ilya G.; Rozhnov, Viatcheslav V. (Zootaxa, 2009)
The taxonomic status of the harvest mouse Micromys minutus from Vietnam is re-evaluated. The mtDNA analysis shows that the harvest mice from Lao Cai Province of northern Vietnam belongs to a distinct phylogenetic lineage, previously known only from a haplotype from Chengdu, Sichuan Province, southern China (Yasuda et al. 2005). The mtDNA analysis shows a strong genetic divergence among this lineage and all the other known haplotypes of Micromys minutus (11.68% for cytochrome b gene sequences). Canonical discriminant analysis of cranial and dental data, as well as of some external characters, also separate the Vietnam – South China group (also including an Indian specimen) from other Palaearctic populations. The skull of southern populations is relatively large, with a longer and broader palatine. The dorsal pelage of the Vietnamese specimens is grey, tinged with brown in comparison with the red-brown dorsal colouration sharply contrasting with the white underside in the majority of Euro-Siberian adults. The harvest mice of the Vietnam – South China group are distinguished from the typical European ones by their rather long tail that is about 120% of the body length (82 to 95% in the Palaearctic populations). Both genetic and morphological data suggest the existence of a second Micromys species, occurring at least in North Vietnam and South China. The available name for this species is Micromys erythrotis (Blyth, 1856).